THE PROFESSIONAL LEARNING COMMUNITY MANAGEMENT MODEL FOR DEVELOPMENT OF ACTIVE LEARNING MANAGEMENT IN DIGITAL ERA - BOONKHUM RATBUMRUNG SCHOOL, PATHUMTHANI PRIMARY EDUCATION SERVICE AREA OFFICE 1 - Prapainop , Surang (Journal of MCU Nakhondhat, 2023)
The objectives of the research are: 1) to determine factors that compose the Professional Learning Community Management Model for Development of Active Learning Management in Digital Era. 2) to develop a the Professional Learning Community Management Model for Development of Active Learning Management in Digital Era. 3) to confirm the Professional Learning Community Management Model for Development of Active Learning Management in Digital Era. 4) to study the result of implementing t the Professional Learning Community Management Model for Development of Active Learning Management in Digital Era by using mixed methods research, i.e., analyzing research documents and publications, expert interviews, three rounds adjustment by Modified Delphi techniques, and survey technique. The selected population for this research was 55 management and teachers of Boonkhumratbumrung School. Tools used for data collection are questionnaires for content analysis, structural interviews, rating scale questionnaires, and checks list. The research found that: 1. The Professional Learning Community Management Model for Development of Active Learning Management in Digital Era has two components which are: Managerial component, there are seven factors, i.e., 1) Leadership, 2) knowledge and professional development, 3) community relationship, 4) teamwork, 5) shared vision, 6) structure of professional learning community and 7) digital technology and its development and development of proactive learning component, there are two factors, i.e., 1) the ability to develop lesson plan and 2) the ability to implement active learning in teaching. 2. The implementation results of the model confirms that it is possible and appropriate to apply the model at higher level.